MALAYSIAN ISLAMIC SECONDARY SCHOOL LEADERS’: LEADERSHIP CHALLENGES - Zunaidi Haruna; Muhammad Faizal A Ghanib; Abd. Muhith; Muh Ibnu Sholeh; Hepni (Jurnal Tinta, 2024)
This study aims to explore the Malaysian Islamic secondary school (SMA) leaders’ leadership challenges. To respond to the study aim, a qualitative method using interview was applied to seven leaders of Islamic Secondary Schools. The informers were selected based on some criteria such as the length of service as a leader and leadership knowledge. The data that were analysed using thematic analysis reported seven challenges of Malaysian Islamic secondary school leaders’ leadership, namely: (i) lack of knowledge, in particular, the field of school management such as finance, IT, asset, data and information, (ii) lack of management skill to figure out conflicts regarding incentive differences among senior and novice teachers, (iii) lack of collaboration among stakeholders, (iv) need to allocate more finance for the competency development programme such as enhancing novice teachers’ pedagogical skills, (v) Inadequate planning of valuable programme for students residing in hostel, (vi) less concern to support some Ministry of Education’s policies, and (vii) less concern on the changing environment, in particular, the field of pedagogical changes for the post of COVID-19 pandemic. The implication of this study is to be aware for the educational stakeholders, in particular, the school leaders, to take into account this study findings in order to make self-improvement for enhancing the students learning and school achievement